Global Characteristics of CSIG-Associated Gene Expression Changes in Human HEK293 Cells and the Implications for CSIG Regulating Cell Proliferation and Senescence - Ma, Liwei; Zhao, Wenting; Zhu, Feng; Yuan, Fuwen; Xie, Nan; Li, Tingting; Wang, Pingzhang; Tong, Tanjun (Frontiers in Endocrinology, 2015)
Cellular senescence-inhibited gene (CSIG), also named ribosomal_L1 domain-containing 1 (RSL1D1), is implicated in various processes including cell cycle regulation, cellular senescence, apoptosis, and tumor metastasis. However, little is known about the regulatory mechanism underlying its functions. To screen important targets and signaling pathways modulated by CSIG, we compared the gene expression profiles in CSIG-silencing and control HEK293 cells using Affymetrix microarray Human Genome U133 Plus 2.0 GeneChips. A total of 590 genes displayed statistically significant expression changes, with 279 genes up-regulated and 311 down-regulated, respectively. These genes are involved in a broad array of biological processes, mainly in transcriptional regulation, cell cycle, signal transduction, oxidation reduction, development, and cell adhesion. The differential expression of genes such as ZNF616, KPNA5, MAP3K3 were further validated by real-time PCR and western blot analysis. Furthermore, we investigated the correlated expression patterns of ESCO1, KPNA5, MAP3K3 and CSIG during cell cycle and senescence progression, which imply the important pathways CSIG regulating cell cycle and senescence. The mechanism study showed that CSIG modulated the mRNA half-life of Cdc14B, CASP7 and CREBL2. This study shows that expression profiling can be used to identify genes that are transcriptionally or post-transcriptionally modified following CSIG knockdown and to reveal the molecular mechanism of cell proliferation and senescence regulated by CSIG.